Academic Labour Markets: Perspectives from Ontario - Rosenblum, Gerald; Rosenblum, Barbara Rubin (Canadian Journal of Higher Education, 1994)
Segmented labour market thinking is utilized, as are working definitions of internal and external labour markets relative to the university as employing organization, in a study of the deployment of instructional staff at one mid-sized Ontario university. Specific categories of students are found to be dispropor- tionately served by members of one or another of these market segments. Pronounced differences are discerned with respect to age and gender relative to labour market location. Statistics Canada data are utilized to demonstrate wide variations in the use of external labour market instructors over time within and between universities. Implications are discussed.